Dynamic Posterior Stabilization versus Posterior Lumbar Intervertebral Fusion: A Matched Cohort Study Based on the Spine Tango Registry - Bieri, Kathrin S.; Goodwin, Kelly; Aghayev, Emin; Riesner, Hans-Joachim; Greiner-Perth, Ralph (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Purpose The primary aim of dynamic stabilization is to stabilize the spine and preserve function without overstressing adjacent segments, which is a potential risk of fusion surgery. However, direct comparative analyses of the two approaches are still limited, and little is known about the association of patient-reported outcomes with these treatment options.Objective To compare the clinical outcomes of dynamic posterior stabilization using the DSS Stabilization System (Paradigm Spine, LLC, New York, New York, United States) versus posterior lumbar intervertebral fusion (PLIF) based on data from a spine registry. We hypothesized that patient-reported outcomes of DSS are not inferior to those of PLIF.Methods We identified 202 DSS and 269 PLIF patients with lumbar degenerative disease with a minimum 2-year follow-up. A 1:1 propensity score–based matching was applied to balance the groups for various patient characteristics. The primary outcome was the change in the patient-reported Core Outcome Measures Index (COMI; a 0–10 scale) score.Results The matching resulted in 77 DSS-PLIF pairs (mean age: 67 years; average COMI follow-up: 3.3 years) without residual significant differences in baseline characteristics. The groups showed no difference in improved COMI score (p = 0.69), as well as in back (p = 0.51) and leg pain relief (p = 0.56), blood loss (p = 0.12), and complications (p > 0.15). Fewer repeat surgeries occurred after DSS (p = 0.01). The number of repeat surgeries per 100 observed person-years was 0.8 and 2.9 in DSS and in PLIF patients, respectively. Furthermore, shorter surgery time (p < 0.001) and longer hospital stays (p = 0.03) were observed for DSS cases.Conclusion In a midterm perspective, DSS may be a viable alternative to PLIF because both therapies result in similar COMI score improvement. Advantages of DSS may be shorter duration of surgery and fewer repeat surgeries. However, more than half of DSS patients did not find a match with a PLIF patient, suggesting that the patient profiles may be different. Further multicenter studies are needed to better understand the most appropriate indication for each therapy.
Keywords: dynamic stabilization; fusion; degenerative spine disease; propensity score-based matching; registry